2019
DOI: 10.11607/jomi.7275
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Leukocyte- and Platelet-Rich Fibrin Block: Release of Growth Factors, Cellular Content, and Structure

Abstract: Purpose:The Leucocyte and Platelet Rich Fibrin Block (L-PRF Block) is a composite graft that combine a xenograft that is acting as a scaffold with L-PRF membranes that serve as a bioactive nodule with osteoinductive capacity. This study evaluated the properties of the L-PRF Block and its components in terms of release of growth factors, cellular content and structure. Methods:The concentration of transforming growth factor-β1 (TGF-β1), vascular endothelial growth factor (VEGF), platelet-derived growth factor-A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
57
1
8

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(71 citation statements)
references
References 37 publications
5
57
1
8
Order By: Relevance
“…It has to be underlined, however, that those authors did not analyze the secretion of PDGF-BB, as we did. In our experimental conditions, after PDGF-BB, the most expressed factor was TGF-β, in accordance with Castro et al [31].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…It has to be underlined, however, that those authors did not analyze the secretion of PDGF-BB, as we did. In our experimental conditions, after PDGF-BB, the most expressed factor was TGF-β, in accordance with Castro et al [31].…”
Section: Discussionsupporting
confidence: 92%
“…A cumulative analysis for all donors at all time points revealed that PDGF-BB was the growth factor present at the highest concentration in the liquid fibrinogen, unlike another study in which TGF-β1 was the most released [31]. It has to be underlined, however, that those authors did not analyze the secretion of PDGF-BB, as we did.…”
Section: Discussioncontrasting
confidence: 68%
“…Different groups have measured specific growth factors released by PRC, compared their enrichment in different types of PRC and measured their kinetics over time 18,19,22,23 . Nevertheless, the total secretome released by PRC has not been yet analysed in detail.…”
Section: Discussionmentioning
confidence: 99%
“…Numerosos son los usos clínicos descritos en la abultada literatura disponible actualmente para los concentrados plaquetarios, siendo quizás la reconstrucción de rebordes alveolares atróficos ( Fig. 1) como preparación previa a la instalación de implantes óseo integrados su principal indicación (Castro et al, 2019).…”
Section: Aplicaciones Clínicas De Los Concentra-dos Plaquetariosunclassified